Aversion to In-vehicle Crowding before, during and after the COVID-19 Pandemic - Stefan Flügel; Nina Hulleberg (Findings)
Based on four consecutive stated choice surveys, we estimate changes in public transport user's valuation (marginal costs) of in-vehicle crowding due to the COVID-19 pandemic in two Norwegian cities. Compared to the pre-COVID level (November 2018), we find significantly higher costs during COVID (November 2021). Post-COVID costs (May 2022) are significantly reduced but remain above the pre-COVID level.